Quality of life among cancer patients undergoing chemotherapy in government hospitals in Peninsular Malaysia - Subramaniam, Suhasinee (2018)
INTRO : Cancer is an important health concern globally and is one of the leading causes of morbidity and mortality worldwide. According to the World Health Organization (WHO), cancer is the second leading cause of death globally. An analytic cross-sectional study was conducted to determine the predictors of quality of life among chemotherapy cancer patients in government hospital in Malaysia. Cancer patients undergoing chemotherapy treatment in ten state government hospitals in Peninsular Malaysia were included in this study. Patients who did not give consent to participate in this study or who were absent during the data collection period were excluded. METHODS : The data were collected using self-administered questionnaires including socio-demographic characteristics, quality of life (WHOBREF), social support (Multidimensional Scale of Perceived Social Support (MSPSS)), hopelessness (The Beck Hopelessness Scale (BHS) and physical effect (Common Terminology Criteria for Adverse Events (CTCAE) version 4.0) Data were analyzed using the statistical computer software of SPSS version 23. Descriptive statistics were conducted to obtain frequency and percentage of variables. Independent sample T-test and One way ANOVA were used to determine the association between variables at level of significance, p<0.25.Continuous variables were presented as means with 95% Confidence interval (CI). Multiple linear regression model was used to determine the significant predictors. A p-value of less than 0.05 was considered statistically significant. The predictors of each domain was analysed separately. RESULTS : Quality of life among cancer patients undergoing chemotherapy in this study was determined by four domains which were physical health, psychological, social relationships and environment. The overall mean score for physical health was 52.60, psychological was 52.55, social relationships was 50.79 and environment was 51.16. All 1333 chemotherapy patients completed the questionnaire in this study; giving a response rate of 100 %. Majority (61.0%) of patients were Malay female patients. Meanwhile 1021 patients (51.2%) received high social support and 38.0% of patients had moderate level of hopelessness in determining quality of life in patients. Highest number of patients (51.5%) were affected due to mild skin nail changes during chemotherapy and (31.4%) was affected with mild anorexia and vomiting in chemotherapy. DISCUSSION : The significant predictors of physical effect domain were monthly income, cancer stage, social support, nausea and vomiting. The significant predictors of psychological domain were race, marital status, cancer stage, nausea and vomiting. The significant predictors of social relationships domain were race, educational level, social support, nausea and vomiting. The significant predictors of environment domain were race, marital status, hopelessness level, nausea and vomiting. CONCLUSION : The quality of life among chemotherapy cancer patients is important to be observed. Based on the predictors found in this study, appropriate interventions can be taken to improve the quality of life outcomes and the response towards the treatment.